2021
DOI: 10.1186/s10033-021-00552-9
|View full text |Cite
|
Sign up to set email alerts
|

Chip Formation Mechanism of Inconel 718: A Review of Models and Approaches

Abstract: Inconel 718, a nickel, chrome and iron alloy, has special advantages, such as high-temperature strength, thermal resistance and corrosion resistance, which facilitate wide usage in the aerospace industry, especially in the hot sections of gas turbine engines. However, machining this alloy is correlated closely with the material’s inherent properties such as excellent combination of strength, hardness and toughness, low thermal conductivity and the tendency to adhere to cutting tools. This nickel alloy also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 137 publications
0
13
0
Order By: Relevance
“…In addition, periodic adiabatic shear bands and micro-cracks were observed in the serrated chips. The serrated chips were micro-cracks on the chip-free surface caused by material extrusion [ 31 ], which induced the formation of shear bands. During micro-grooving, the reduction in the load carrying capacity of the material caused the shear band workpiece to move upward and forward in the nodules, eventually forming a complete serrated chip.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, periodic adiabatic shear bands and micro-cracks were observed in the serrated chips. The serrated chips were micro-cracks on the chip-free surface caused by material extrusion [ 31 ], which induced the formation of shear bands. During micro-grooving, the reduction in the load carrying capacity of the material caused the shear band workpiece to move upward and forward in the nodules, eventually forming a complete serrated chip.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the raw material procurement, supply, and production process of general sintering plants are relatively stable. Liu et al [ 43 ] systematically calculated and analyzed the sulfur balance in the sintering process based on the production data of the Jingtang Sintering Plant. Subsequently, a relationship between the sulfur content of the sintering raw materials and SO 2 emissions was derived, with a control standard for low sulfur sintering raw materials.…”
Section: Desulfurization Ideas and Methodsmentioning
confidence: 99%
“…The research showed that it was difficult to achieve SO 2 emissions directly by reducing the sulfur content of the raw materials. [43] However, other methods can be used to reduce sulfur input such as the introduction of clean technologies, including high proportion hydrogen-rich fuel sintering, [44] layered heating hydrogen-rich sintering, [45] and hydrogen gas injection. [46] These clean technologies show that not only SO 2 emissions can be reduced, but CO 2 emissions can also be effectively reduced.…”
Section: Desulfurization Ideas and Methodsmentioning
confidence: 99%
“…Priyadarshini et al 66 presented a brief overview of the application of FEM to metal cutting simulation. Recently, a detailed review 67 suggested that the causes and effects of chip segmentation need to be considered in the simulation to improve tool life prediction and select the optimal cutting parameters for improved product quality. Guo et al 68 investigated the chip formation mechanism using FEM considering a damage model.…”
Section: Dynamics Of Chip Formationmentioning
confidence: 99%